The influence of Organizational Culture on the quality of Service in the Department of Population and Civil Registration of Majalengka Regency - Dody Kusmayadi; Tera Triyantara Hani RN (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of organizational culture on the quality of public services in the Department of Population and Civil Registration of Majalengka Regency. The study used a quantitative approach with the type of explanatory research. The study population is all employees Department of Population and Civil Registration of Majalengka Regency with a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using simple linear regression. The results showed that organizational culture is in the category of strong enough, with an average value of 3.87, while the quality of public services is in the category of good, with an average value of 3.92. The results of the regression test showed that organizational culture has a positive and significant effect on the quality of public services with a regression coefficient of 0.53, a t-count value of 4.62, and a significance level of 0.000 ( 0.05). The value of the coefficient of determination of 0.28 indicates that organizational culture is able to explain 28% variation in the quality of public services. This study confirms that the strengthening of organizational culture is an important factor in improving the quality of public services.